Linearization-Based Word-Part Ellipsis - Chaves, Rui P. (Linguistics and philosophy, 2008)
This paper addresses a phenomenon in which certain word-parts can be omitted. The evidence shows that the full range of data cannot be captured by a sublexical analysis, since the phenomena can be observed both in phrasal and in lexical environments. It is argued that a form of deletion is involved, and that the phenomena—lexical or otherwise—are subject to the same phonological, semantic, and syntactic constraints. In the formalization that is proposed, all of the above constraints are cast in a parallel and declarative fashion, in the framework of Head-Driven Phrase Structure Grammar (Pollard and Sag Head-driven phrase structure grammar, 1994), since the various levels of linguistic description are locally and simultaneously available. Building on recent accounts of ellipsis, this paper proposes a unified and general account of word-part ellipsis and phrasal ellipsis.